Incidence and causes of lower-limb amputations in the city of Ribeirão Preto from 1985 to 2008: evaluation of the medical records from 3,274 cases - Bruna Maria Bueno Barbosa; Rosane Aparecida Monteiro; Lucas Françolin Sparano; Rodolfo Fabiano Niz Bareiro; Afonso Dinis Costa Passos; Edgard Eduard Engel
ABSTRACT: Objective: It was to identify trends of traumatic and non-traumatic causes of lower limb amputations, as well as the role played by population aging, traffic violence increase, public health policy of diabetes control program and drivers anti-alcohol laws on these amputations. Method: Hospitalization data recorded in the discharge forms of 32 hospitals located in the region of Ribeirão Preto, Brazil, from 1985 to 2008 were analyzed. Result: A total of 3,274 lower-limb amputations were analyzed, of which 95.2% were related to non-traumatic causes, mainly infectious and ischemic complications of diabetes mellitus. Cancer (2.8%) and congenital (1.3%) causes were included in this group. Only 4.8% were related to traumatic causes. Traumatic amputation average rate was 1.5 amputations in 100,000 habitants with a slight tendency of increase in the last 5 years. Non-traumatic causes showed an average rate of 30.0 amputations for 100,000 habitants and remained relatively constant during the whole period. Non-traumatic were much more predominant in patients older than 60 years and traumatic amputations occurred more frequently in patients younger than 39 years. Conclusion: The overall rates of amputation and the rates of traumatic and non-traumatic amputations remained nearly constant during the study period. The impact of diabetes control policies and the introduction of traffic safety laws could not be identified on the amputation rates.